Case Studies of Transdisciplinary Approach in Vocational Schools: Student Business Center Program - Vachruddin, Vrisko Putra; Setiawan, Agus; Asrohah, Hanun; Haq, Nadya Isabel (Universitas Ahmad Dahlan, 2024)
The transdisciplinary approach to project-based learning is very interesting to study. Collaboration between several sciences produces integrated scientific products that will improve students' ability to solve a problem based on collaboration of scientific perspectives. Vocational schools that have a vision to produce competent and skilled experts in their fields must provide a foundation of other sciences in order to create quality human resources. This study attempts to collaborate several sciences (transdisciplinary) through project-based learning with the team-teaching method. This study also describes the stages in a case study of the transdisciplinary approach at one of the vocational schools with an excellent program (SMK center of excellence) in Sidoarjo Regency, Indonesia. This type of research is included in descriptive qualitative research with a case study approach. There are several problems in implementing the transdisciplinary approach to the student business center (SBC) program, namely: lack of time to collaborate, group dynamics played by some teachers are less effective, overlapping roles and inadequate funding. However, through the formation of teams in the classroom in a balanced manner, students can learn tolerance with peers, learn leadership skills and collaboration between teams. In addition, through a transdisciplinary approach, students will learn about the democracy of the learning environment by valuing their voices and teachers who empower them as students. The results of the evaluation related to the student business center (SBC) program through the distribution of questionnaires to students with 19 learning response indicators showed a figure of 65% or in the good category.